(untitled) (Bioscience Journal, 2022)
Solanum capsicoides, commonly known as red soda apple, is a little-studied species with phytotherapeutic characteristics of interest to the pharmaceutical industry. However, little is known about its agronomic characteristics. Therefore, this study aimed to assess the effect of light, different temperatures, and substrates on the germination of S. capsicoides seeds. The study consisted of two experiments: Experiment I - Germination of S. capsicoides seeds under different wavelengths. The seeds were kept on Petri dishes covered with Germitest™ paper moistened with distilled water and exposed to the monochromatic, red, far-red, and dark wavelengths. The experiment was performed in a completely randomized design with four replications of 25 seeds. Experiment II - Germination of S. capsicoides seeds on different substrates and at different temperatures. The seeds were distributed according to six substrates: paper roll, on paper, between sand, on sand, on soil + sand + manure, and between soil + sand + manure. The seeds were also subjected to the constant temperatures of 20, 25, 30, and 35 °C and the alternate temperatures of 20-30, 20-35, 25-30, and 25-35 °C, characterizing a 6 x 8 factorial arrangement. Germination rate, germination speed index, and mean germination time were evaluated. Red soda apple seeds are classified as positive photoblastic, with the highest germination rate occurring at the temperature of 20-35 °C combined with on paper, paper roll, on sand, and between sand substrates.